2013
DOI: 10.1002/emmm.201201876
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 activity is necessary and sufficient for the development of immune‐mediated myocarditis in mice and promotes progression to dilated cardiomyopathy

Abstract: Myocarditis, often triggered by viral infection, may lead to heart auto-immunity and dilated cardiomyopathy. What determines the switch between disease resolution and progression is however incompletely understood. We show that pharmacological inhibition of STAT3, the main mediator of IL-6 signalling and of Th17-cell differentiation, protects mice from the development of Experimental Auto-immune Myocarditis reducing liver production of the complement component C3, and can act therapeutically when administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
(101 reference statements)
6
35
1
Order By: Relevance
“…ALK-, C/EBPb-, and Stat3-specific shRNAs have been previously described (23,24). Retrovirus expressing NPM-ALK (25), STAT3C (26) or lentivirus expressing C/EBPb (23) have been previously described.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…ALK-, C/EBPb-, and Stat3-specific shRNAs have been previously described (23,24). Retrovirus expressing NPM-ALK (25), STAT3C (26) or lentivirus expressing C/EBPb (23) have been previously described.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…[1][2][3] In oncology, monomeric and polymeric anti-epidermal growth factor receptor (EGFR) and anti-CD20 IgAs have demonstrated superior tumor cell killing compared to IgG, driven by FcαRI-mediated cytotoxicity or more effective receptor binding and downmodulation. [4][5][6] The cytotoxic activity of IgA could be further increased via dual engagement of both FcγR and FcαRI by IgG/A fusion or hybrid molecules. 7,8 For infectious disease, IgA multivalent target engagement enabled superior antigen binding and neutralization in influenza infection models.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 in particular mediates a signal transduction that promotes cellular growth and reverses apoptosis, and thus plays a key role in neovascularization and cellular survival. Studies have shown that deletion of STAT3 in mice causes cardiomyopathy (14), and in patients with the disease, the level of STAT3 in the myocardia was significantly low (15). All these suggest that activating the JAK/STAT3 pathway may be the key to preventing the onset of heart failure.…”
Section: Discussionmentioning
confidence: 99%